Prognostic impact of chronic obstructive pulmonary disease in patients with heart failure with mildly reduced ejection fraction - Lau, Felix; Schupp, Tobias; Schmitt, Alexander; Reinhardt, Marielen; Abel, Noah; Abumayyaleh, Mohammad S. A.; Weidner, Kathrin; Dürschmied, Daniel; Ayoub, Mohamed; Mashayekhi, Kambis; Akin, Muharrem; Ayasse, Niklas; et al. (Respiratory medicine, 2024)
Background - The aging population has led to a significant increase in heart failure (HF) patients. Related to demographic changes, the burden with comorbidities was shown to increase in patients with HF. Whereas chronic obstructive pulmonary disease (COPD) was yet demonstrated to be associated with adverse outcomes in patients with HF, the prognostic impact of COPD in HF with mildly reduced ejection fraction (HFmrEF) has not yet been clarified. - Objective - The study investigates the prognostic impact of COPD in patients hospitalized with HFmrEF. - Methods - Consecutive patients with HFmrEF were retrospectively included at one institution from 2016 to 2022. Patients with COPD were compared to patients without with regard to the primary endpoint all-cause mortality at 30 months (median follow-up). Secondary endpoints comprised in-hospital mortality, HF-related re-hospitalization, cardiac re-hospitalization and major adverse cardiac and cerebrovascular events (MACCE) at 30 months. - Results - A total of 2184 patients with HFmrEF were included with a prevalence of COPD of 12.0 %. Patients with COPD were older (median 77 vs. 75 years; p = 0.025), had increased burden of cardiovascular comorbidities and more advanced HF symptoms. At 30 months, patients with COPD had an increased risk of all-cause mortality compared to patients without (45 % vs. 30 %; HR = 1.667; 95 % CI 1.366-2.034; p = 0.001), alongside with a higher risk of re-hospitalization for worsening HF (20 % vs. 12 %; HR = 1.658; 95 % CI 1.218-2.257; p = 0.001). - Conclusion - COPD is independently associated with adverse outcomes in patients hospitalized with HFmrEF.